2018
DOI: 10.4102/hts.v74i3.5013
|View full text |Cite
|
Sign up to set email alerts
|

Moving from faith-based concerns to demarginalising youths through the Circle of Courage

Abstract: Although the demarginalisation of youths is an international concern, South African youths are viewed by various scholars and policy documents as a particularly vulnerable and marginalised group. It becomes essential to understand what characterises their marginalisation in order to find innovative ways to work towards their demarginalisation. In this article we reflect on current faith-based concerns and compare this with the specific characteristics of the marginalisation of young people. In an effort to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This is supported by various statistics stating that the youth are the most vulnerable group in South Africa and the rest of the world (cf. Aziz, 2020;Swart, 2018;Swartz & Nyamnjoh, 2018;Beukes & Van der Westhuizen, 2018;Nel, 2014Department of Social Development, 2013). Previous research has also shown that youth even feel vulnerable and excluded within the church and certain church structures (Beukes & Van der Westhuizen, 2016;Voas & Watt, 2014;King, 2012).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…This is supported by various statistics stating that the youth are the most vulnerable group in South Africa and the rest of the world (cf. Aziz, 2020;Swart, 2018;Swartz & Nyamnjoh, 2018;Beukes & Van der Westhuizen, 2018;Nel, 2014Department of Social Development, 2013). Previous research has also shown that youth even feel vulnerable and excluded within the church and certain church structures (Beukes & Van der Westhuizen, 2016;Voas & Watt, 2014;King, 2012).…”
Section: Introduction Introductionmentioning
confidence: 99%